2010
DOI: 10.1007/s00127-010-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in Ecuadorian migrants from a population-based survey: the importance of social determinants and gender roles

Abstract: Mental health in Spanish and Ecuadorian women living in Spain is poorer than men. Ecuadorian women are the most disadvantaged group in terms of prevalence of and risk factors for PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…The limited number of studies that found an association between migration and common mental disorders was based on international migration and settings different from Peru [12, 2628], including a recent study of Ecuadorian migrants living in Spain [29]. This discordance may be due to the heterogeneity of the definition of “migrant”, including labor migrants and/or refugees, and the use of different tools to measure common mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of studies that found an association between migration and common mental disorders was based on international migration and settings different from Peru [12, 2628], including a recent study of Ecuadorian migrants living in Spain [29]. This discordance may be due to the heterogeneity of the definition of “migrant”, including labor migrants and/or refugees, and the use of different tools to measure common mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…I alt ble 151 artikler lest i sin helhet, hvor av 92 oppfylte de opprinnelige inkluderingskriteriene (Aalto et al, 2014;Agudelo-Suarez et al, 2013;Agudelo-Suarez et al, 2011;Ahonen & Benavides, 2006;Alexe et al, 2003;Bergbom & Kinnunen, 2014;Bergbom et al, 2015;Bhui et al, 2005;Biering et al, 2016;Borrell et al, 2008;Cayuela et al, 2015;C. Chen et al, 2010;Chowhan, 2016;Connell et al, 2007;Cross & Turner, 2013;Davidson & Orr, 2009;Del Amo et al, 2011;Diaz-Serrano, 2013;Dunlavy et al, 2016;Dunlavy & Rostila, 2013;Elders et al, 2004;Font, Moncada, Llorens, et al, 2012;Frickmann et al, 2012;Gil-Gonzalez et al, 2014;Hogh et al, 2011;Hoppe, 2011;Johansson et al, 2012;Jonson & Giertz, 2013;Jorgensen et al, 2011;Krings et al, 2014;Kuusio et al, 2013;Mastrangelo et al, 2010;Miller & Travers, 2005;Nieuwenhuijsen et al, 2015;Olesen et al, 2012a;Olesen et al, 2012b;Pasca & Wagner, 2012;Perez-Carceles et al, 2014;Pikhart et al, 2010;Premji et...…”
Section: Resultatermentioning
confidence: 99%
“…Fire undersøkelser av den generelle yrkesbefolkningen i Spania rapporterte høyere forekomst av psykiske plager blant kvinnelige innvandrerer (Cayuela et al, 2015;Del Amo et al, 2011;Vives et al, 2013), og blant mannlige og kvinnelige innvandrere , sammenliknet med øvrige sysselsatte. Høyere nivåer av psykiske plager blant innvandrere er også rapportert i undersøkelser av den generelle yrkesbefolkningen i Sverige (Dunlavy & Rostila, 2013) og Nederland (Nieuwenhuijsen et al, 2015), en studie av sykehusansatte i Tyskland (Sieberer et al, 2012) og en studie av renholdsarbeidere i Norge (Gamperiene et al, 2006).…”
Section: Selvvurdert Helse (Srh) Og Symptomer På Psykiske Plagerunclassified
“…However, evidence on the actual prevalence of psychological disorders in this population is inconclusive with studies reporting higher [ 129 , 132 , 133 ], similar [ 134 ], and lower rates [ 135 ] vs local populations. Differing patterns have also been found when disaggregating the analysis by sex [ 136 ] and country of birth [ 137 ], including reports of wide disparities in antidepressant consumption [ 138 ].…”
Section: Resultsmentioning
confidence: 99%